Legal perspectives on sustainability - Pieraccini, Margherita; Novitz, Tonia (Bristol : Bristol University Press, 2020)
This important volume steps beyond conventional legal approaches to sustainability to provide fresh insights into perhaps one of the most critical global challenges of our time. Offering analysis of sustainability at land and sea alongside trade, labour and corporate governance perspectives, this text articulates important debates about the role of law. From impacts on local societies to domestic sustainable development policies and major international goals, it considers multiple jurisdictional levels.
Also issued in print: 2020.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on August 11, 2020).
Keywords: Environmental law; Sustainability; Commercial law; Law; Laws of specific jurisdictions & specific areas of law